THE ROLE OF INFORMATION TECHNOLOGY IN BOOSTING ECONOMIC GROWTH IN BORDER TERRITORIES - Melyana R Pugu; Diego Romario De Fretes; Meyland S. F. Wambrauw (Adisam Publisher, 2024)
Border territories have strategic values in supporting the success of national development. One effort to improve the economy of border region communities is through empowering micro, small and medium businesses so as to encourage economic growth. Information technology introduces new opportunities and problems that are distinct from traditional approaches, changing the way business is conducted. One of the primary pillars supporting the modern civilization's progress is information technology, which has to be able to benefit the larger community. Border regions are increasingly being the focus of development efforts across all domains in the context of fair development. The research was carried out using the literature study method. This research discusses the definition of information technology and border areas, the relationship between information technology and economic growth, the concept of economic growth in border areas, the concept of the use of information technology to encourage economic growth, the relationship between economic growth in border areas and the use of information technology, and research implications for policy development.